2016
DOI: 10.1021/acsami.5b11258
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hydrophilic CuInS2/ZnS Quantum Dots with Different Polymeric Shells and Study of Their Cytotoxicity and Hemocompatibility

Abstract: In this work, there is a detailed description of the whole process of biocompatible CIS/ZnS QDs production. Special attention was paid to the stability of QDs against photooxidation. It was shown that Cu/In ratio greatly affected not only nanocrystals PLQYs but photostability as well. CIS/ZnS QDs with Cu/In = 1:4 ratio showed high photostability under UV illumination both in toluene and aqueous solutions. Meanwhile, photoluminescence of CIS/ZnS QDs with Cu/In = 1:1 ratio was completely quenched after several h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
0
38
2
Order By: Relevance
“…Thus, the development of novel QDs with extremely low cytotoxicity (especially Cd-free alternatives) is necessary for further advancement of QD technology15161718. There have been some reports about the cadmium-free QDs such as carbon or CuInS 2 /ZnS QDs192021. We previously reported the facile synthesis of ZnS-AgInS 2 (ZAIS) as a cadmium-free QD, and confirmed that ZAIS was useful as a color-adjustable fluorophore mainly for solar cells2223.…”
mentioning
confidence: 89%
“…Thus, the development of novel QDs with extremely low cytotoxicity (especially Cd-free alternatives) is necessary for further advancement of QD technology15161718. There have been some reports about the cadmium-free QDs such as carbon or CuInS 2 /ZnS QDs192021. We previously reported the facile synthesis of ZnS-AgInS 2 (ZAIS) as a cadmium-free QD, and confirmed that ZAIS was useful as a color-adjustable fluorophore mainly for solar cells2223.…”
mentioning
confidence: 89%
“…The X-ray absorption near-edge structure (XANES) results demonstrated the high chemical stability of CIS and CIS/ZnS QDs in Caenorhabditis elegans for a range of exposure times. Speranskaya et al has studied the photostability and cytotoxicity of CIS/ZnS heterostructures [190]. It was found that the photostability of CIS/ZnS core-shell structures under constant UV illumination depends on the Cu/In ratio used for CIS core synthesis.…”
Section: Applications Of Cu-based Ternary or Quaternary Quantum Namentioning
confidence: 99%
“…20 Nevertheless, to date high PLQYs (≥50%) have only been reported for CIS/ZnS and CIS/CdS core/shell QDs with core diameters below 4 nm and PL up to 750 nm. 1719,2124 Although luminescent CIS QDs larger than 4 nm have also been reported, 21,2527 their size and shape dispersion is typically quite large due to the difficulty in balancing the reactivities of multiple precursors (In, Cu, S). 20 Partial topotactic Cu + for In 3+ cation exchange (CE) in template Cu 2- x S nanocrystals (NCs) has been recently established as an effective strategy to circumvent these limitations, 28,29 allowing the preparation of monodisperse luminescent CIS QDs and NCs of sizes and shapes that would not be easily attainable by direct routes.…”
Section: Introductionmentioning
confidence: 99%
“…Overgrowth of a zinc blende ZnS shell on CP CIS QDs has been shown to effectively passivate these surface defects, thereby increasing the PLQYs to values as high as 80%, while excellent stability is imparted with preservation of the inherently low toxicity of CIS QDs. 1719,22,23,27 However, ZnS shelling protocols for WZ CIS QDs are still underdeveloped, as the highest PLQY reported to date for WZ CIS/ZnS QDs is only 1%. 30,32 …”
Section: Introductionmentioning
confidence: 99%